Peningkatan Hasil Belajar Tematik Subtema Tugasku Sehari-Hari Di Rumah Menggunakan Model Pembelajarann Kooperatif Tipe Make A Match Pada Siswa Kelas II SD Ngeri 013 Rokan IV Koto. - Fahrizal, Fahrizal (Faculty Of Education, 2024)
This research was carried out because of the poor learning results of students of second grade SD State 013 Rokan IV Koto on the learning of 3 sub-themes of my daily tasks at home. Based on the results of pre-cycle activities, of 12 students, only 6 students are qualified in subjects of Indonesian language and 3 students in maths. The method used by the researchers in the study of action in this class is the Kurt Lewin model which contains four (four) stages of planning, action, observation, and reflection. The subject of this study is a student of 2nd grade SD State 013 Rokan IV Koto consisting of 12 students. The results of the study showed that: 1) the application of the cooperative model of the Make a Match type can improve the activity of teachers and students. On the observation results of teacher activity in cycle I was 72,52, and increased to 90,32 in the second cycle. whereas the observations of student activity in the first cycle was 70,83, and rose to 91.7 in the Second cycle.) 2) The improvement in student learning outcomes can be seen from the average student score of pre-cycle Indonesian language subjects in the pre cycle of 66.08 with a percentage of 50%, in the 1st cycle to 75 with a percent 66.66%, and increases to 78.91 with a procent of 83.33% in the 2nd cycle. In the mathematics subject also increased i.e. pre- cycle by 61.33, with 33.33 percent, in the I cycle became 80.5 with 58.33%, and rised to 77, with a cent of 83,33% In cycle II.